Enthalpies of solution of 1-ethyl- and 1-butyl-3-methylimidazolium based ionic liquids in tetrahydrofuran and chloroform at 298.15K: Thermochemical proton acceptor scale of anions - Khachatrian, Artashes A.; Varfolomeev, Mikhail A.; Akhmadeev, Bulat S. (Thermochimica acta, 2016)
[Display omitted] •Enthalpies of solution of 9 ionic liquids in tetrahydrofuran and chloroform were measured at 298.15K.•Enthalpies of solution in chloroform were exothermic due to hydrogen bonging.•Proton acceptor scale of imidazolium based ionic liquids were proposed.•Greatest enthalpies of hydrogen bonding were obtained for ionic liquids with alkylsulfate anions.•Correlation between calorimetric hydrogen bonding enthalpies and COSMO-RS hydrogen bonding energies was observed. In this work the thermodynamics of intermolecular interactions for imidazolium based ionic liquids in solutions of proton donor solvent chloroform and proton acceptor solvent tetrahydrofuran was studied using solution calorimetry technique. Enthalpies of solution of 1-ethyl- and 1-butyl-3-methylimidazolium based ionic liquids with tetrafluoroborate, methylsulfate, ethylsulfate, butylsulfate, dicyanoamide, trifluoromethanesulfonate, thiocyanate anions were measured in two solvents over concentration range 0.18-3.60mmolkg−1 at 298.15K. Enthalpies of transfer from tetrahydrofuran to chloroform derived from experimental data were exothermic for all studied ionic liquids. Proton acceptor scale of ionic liquids as solutes was proposed on the basis of thermochemical data. Enthalpy of hydrogen bonding of ionic liquids with proton donor solvent chloroform increases in the range of anions [BF4]−<[SCN]−<[TfO]−<[N(CN)2]−<[AlkSO4]−. At the same time these values remain constant for ILs with different length of alkyl group in cations and anions. Thermochemical proton acceptor scale of ILs in solution correlates well with COSMO-RS hydrogen-bonding energies in equimolar cation–anion pairs of ILs.